ASSESSING UNITED STATES GRAND STRATEGY: ESTIMATING THE PATTERN OF UNITED STATES FOREIGN POLICY ON SOUTHEAST ASIA UNDER THE BIDEN PRESIDENCY - Leonard Sebastian; Sigit Nugroho (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
Assessing United States (U.S.) past grand strategy is a useful guide to gauge foreign policy intentions enabling us to gain vital insights to discern the broad pattern of U.S. foreign policy under various administrations. Such an approach can be of benefit to the academic and policy community giving us a sense of the priorities of the foreign policy priorities of the Biden administration particularly with respect to the security of Southeast Asia. With this aim in mind, our article employs a variation of the analytical framework employed in the field of foreign policy evaluation to examine the possible options for U.S. Grand Strategy. At the risk of oversimplification, it selects and assesses four samples of U.S. Grand Strategy alternatives: isolationism, offshore balancing, selective engagement, and deep engagement. Next we focus on recent events to assess which pattern of Grand Strategy best describes the Biden administration’s foreign policy stance. Our aim is that these insights will help regional actors to anticipate and respond accordingly to the Biden administration’s foreign policy stance.